Development of a Fully Implantable Stimulator for Deep Brain Stimulation in Mice - Fleischer, Michael; Endres, Heinz; Sendtner, Michael; Volkmann, Jens (Frontiers in Neuroscience, 2020)
Introduction: Deep Brain Stimulation is an established method for the treatment of neurological and psychiatric disorders. To elicit the underlying mechanisms and explore new stimulation targets, rodent models are necessary. Cable bound external stimulation or portable devices limits movement of the animals and influences behavioral experiments. Therefore, implantable, individually programmed devices are required. Experimental procedure: The stimulator consists of an 8bit-microcontroller mounted on a square electrical board (10x10 mm). External control is enabled by a magnetic reed contact, as running control serves a white LED, running modes are displayed by flash codes. Stimulation parameters could be programmed in the range of pulse width: 60 – 500 µs, amplitude: up to 300 µA and frequency: 10 – 500 Hz. Power is supplied by two standard batteries. The device was implanted in 8-10 weeks old BALBc-mice. Functionality was examined by electrical stimulation of nucleus accumbens area with standard parameters for mice and determination of c-fos levels in-vitro in brain slices. Results: The implanted microstimulator were well tolerated by the mice, without impairment of free movement. Coating, external control and monitoring of function with LED flash code proved to be fully adequate. Stimulation with standard stimulating parameters of nucleus accumbens elicited strong c-fos elevation on simulation site. Conclusion: We present a fully implantable stimulator for freely moving mice that meets the urgent need for further research on the effects of deep brain stimulation in rodent models. It offers the possibility to conduct behavioral experiments for up to 30 days of stimulation.